Identification of Legionella pneumophila-Specific Genes by Genomic Subtractive Hybridization with Legionella micdadei and Identification of lpnE, a Gene Required for Efficient Host Cell Entry - Newton, Hayley J. (American Society for Microbiology, 2006)
Legionella pneumophila is a ubiquitous environmental organism and a facultative intracellular pathogen of humans. To identify genes that may contribute to the virulence of L. pneumophila, we performed genomic subtractive hybridization between L. pneumophila serogroup 1 strain 02/41 and L. micdadei strain 02/42. A total of 144 L. pneumophila-specific clones were sequenced, revealing 151 genes that were absent in L. micdadei strain 02/42. Low-stringency Southern hybridization was used to determine the distribution of 41 sequences, representing 40 open reading frames (ORFs) with a range of putative functions among L. pneumophila isolates of various serogroups as well as strains of Legionella longbeachae, L. micdadei, Legionella gormanii, and Legionella jordanis. Twelve predicted ORFs were L. pneumophila specific, including the gene encoding the dot/icm effector, lepB, as well as several genes predicted to play a role in lipopolysaccharide biosynthesis and cell wall synthesis and several sequences with similarity to virulence-associated determinants. A further nine predicted ORFs were in all L. pneumophila serotypes tested and an isolate of L. gormanii. These included icmD, the 5′ end of a pilMNOPQ locus, and two genes known to be upregulated during growth within macrophages, cadA2 and ceaA. Disruption of an L. pneumophila-specific gene (lpg2222 locus tag) encoding a putative protein with eight tetratricopeptide repeats resulted in reduced entry into the macrophage-like cell line, THP-1, and the type II alveolar epithelial cell line, A549. The gene was subsequently renamed lpnE, for “L. pneumophila entry.” In summary, this investigation has revealed important genetic differences between L. pneumophila and other Legionella species that may contribute to the phenotypic and clinical differences observed within this genus.